Co-precipitation of oppositely charged nanoparticles: the case of mixed ligand nanoparticles. (29th September 2015) - Moglianetti, Mauro; Ponomarev, Evgeniy; Szybowski, Maxime; Stellacci, Francesco; Reguera, Javier
Abstract: Colloid stability is of high importance in a multitude of fields ranging from food science to biotechnology. There is strong interest in studying the stability of small particles (of a size of a few nanometres) with complex surface structures, that make them resemble the complexity of proteins and other natural biomolecules, in the presence of oppositely charged nanoparticles. While for nanoparticles with homogeneously charged surfaces an abrupt precipitation has been observed at the neutrality of charges, data are missing about the stability of nanoparticles when they have more complex surface structures, like the presence of hydrophobic patches. To study the role of these hydrophobic patches in the stability of nanoparticles a series of negatively charged nanoparticles has been synthesized with different ratios of hydrophobic content and with control on the structural distribution of the hydrophobic moiety, and then titrated with positively charged nanoparticles. For nanoparticles with patchy nanodomains, the influence of hydrophobic content was observed together with the influence of the size of the nanoparticles. By contrast, for nanoparticles with a uniform distribution of hydrophobic ligands, size changes and hydrophobic content did not play any role in co-precipitation behaviour. A comparison of these two sets of nanoparticles suggests that nanodomains present at the surfaces of nanoparticles are playing an important role in stability against co-precipitation.